2011
DOI: 10.1017/s0959270911000025
|View full text |Cite
|
Sign up to set email alerts
|

Status assessment of the Critically Endangered Azores BullfinchPyrrhula murina

Abstract: SummaryThe Azores Bullfinch is endemic to the island of São Miguel (Azores, Portugal). Its status was uplisted to Critically Endangered in 2005 on the basis of an extremely small and declining population that was considered to be restricted to a very small mountain range (43 km 2 ), in a single location, within which the spread of invasive plants constituted a threat to habitat quality. Nevertheless, information was mostly inferred, or the product of, non-systematic studies. In order to carry out a complete as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…This recent trend and particularly the Atlas of 2008 have been pivotal to support the IUCN decision of downgrading the conservation status of the Azores Bullfinch from critically endangered to endangered (Ceia et al, 2011a). Based on the Atlases results, it has been suggested that the population have slightly expanded (more individuals, higher density and larger distribution area) between 2008 and 2012.…”
Section: Long Term Population Trend and The Importance Of The Priolo mentioning
confidence: 99%
See 4 more Smart Citations
“…This recent trend and particularly the Atlas of 2008 have been pivotal to support the IUCN decision of downgrading the conservation status of the Azores Bullfinch from critically endangered to endangered (Ceia et al, 2011a). Based on the Atlases results, it has been suggested that the population have slightly expanded (more individuals, higher density and larger distribution area) between 2008 and 2012.…”
Section: Long Term Population Trend and The Importance Of The Priolo mentioning
confidence: 99%
“…It became difficult to observe after 1920, and believed to be almost extinct until the 1960s (Bannerman and Bannerman, 1966;Van Vegten, 1968). The historical decline of this endemic species and its present small range (area of occupancy = 83 km 2 ; Ceia et al, 2011a) likely resulted from the widespread clearance of native forest for pastureland and forestry plantations of Cryptomeria japonica, and more recently, the spread of alien invasive plant species (especially Hedychium gardnerianum, Clethra arborea and Pittosporum undulatum; Ramos, 1995Ramos, , 1996aAubrecht, 2000;Ceia et al, 2011a,b;Gil et al, 2011aGil et al, , 2013Gil et al, , 2014 which replace the natural vegetation, suppressing the native biodiversity ) and reducing the regeneration of the natural vegetation (Ceia et al, 2011b;Heleno et al, 2010). The native laurel forest is now restricted to steep slopes, mostly above 400 m of altitude, limiting the Azores Bullfinch distribution which is entirely dependent on native forest for food during most months of the year (Ramos, 1995;Ceia et al, 2011b).…”
Section: The Azores Bullfinch Conservation Issuesmentioning
confidence: 99%
See 3 more Smart Citations